1988
DOI: 10.1007/bf00199929
|View full text |Cite
|
Sign up to set email alerts
|

The intraperitoneal delivery of radiolabeled monoclonal antibodies: studies on the regional delivery advantage

Abstract: The i.p. delivery of murine monoclonal antibody was compared with i.v. delivery in normal mice and rats, in normal nude mice and in those with i.p. human ovarian carcinoma xenografts. In normal rats, all classes of antibodies and antibody fragments evaluated were cleared from the peritoneal cavity at comparable rates. The regional delivery (Rd1) advantage to the peritoneal cavity following i.p. delivery was thus most dependent on the rate of clearance of the antibody or fragment from the blood stream. Determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 13 publications
0
42
0
Order By: Relevance
“…Because the route of administration and suspension buffer were identical for all IgG preparations, one would expect the kinetics of their i.p. absorption into surrounding tissue and the bloodstream to be equal (36,37). It is unlikely that the high binding V H /V L combinations (IS4VH/B3VL and IS4VHi&ii/B3VL) may have fallen in concentration through binding to other structures during their equilibration phase within the peritoneum because the concentration of these IgG in serum was similar to the low/no CL binding IgG such as IS4VHi&ii/ IS4VL.…”
Section: Discussionmentioning
confidence: 99%
“…Because the route of administration and suspension buffer were identical for all IgG preparations, one would expect the kinetics of their i.p. absorption into surrounding tissue and the bloodstream to be equal (36,37). It is unlikely that the high binding V H /V L combinations (IS4VH/B3VL and IS4VHi&ii/B3VL) may have fallen in concentration through binding to other structures during their equilibration phase within the peritoneum because the concentration of these IgG in serum was similar to the low/no CL binding IgG such as IS4VHi&ii/ IS4VL.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that 111 In-labeled monoclonal antibodies are rapidly absorbed after intraperitoneal injection, with an absorption half-life of 1.9 h that provides a bioavailability of 70% compared with intravenous injection (14). Others have similarly found equivalent blood concentrations at 24 h after intraperitoneal or intravenous injection of radiolabeled antibodies (22). The tumor length and width were measured using calipers.…”
Section: Radioimmunotherapy Studiesmentioning
confidence: 99%
“…In a third group of experiments, mice bearing Daudi tumor cells and treated with CAR ϩ T cells also received human immunoglobulins (Jackson ImmunoResearch). Based on pharmacokinetic studies, 34 we injected the human immunoglobulin 3 times weekly intraperitoneally (100 L at 11 mg/mL). Mouse experiments were performed in accordance with Baylor College of Medicine Animal Husbandry guidelines.…”
Section: In Vivo Study In a Xenogeneic Scid Mouse Modelmentioning
confidence: 99%